Predicting failure modes and load-capacity of fiber-reinforced polymer rods in adhesively bonded anchorages based on numerical modeling. (7th February 2022) - Vo, Van-Nam; Nguyen, Sy-Ngoc; Yoshitake, Isamu
Highlights: The failure modes of FRP rods are predicted based on the maximum stress criterion. The mechanical properties of unidirectional composites are calculated by RVE models. Cohesive zone models are employed to validate the effect of bonding interfaces. The simulation models are employed to predict the load-capacity of FRP rods. The effects of shear-lag, diameter, failure modes on FRP rods are investigated in detail. Abstract: The tensile properties of fiber-reinforced polymer (FRP) rods in adhesively bonded anchorages are expected to be studied in detail. Therefore, the study aims to predict the failure modes and load-bearing capacity (load-capacity) of FRP rods subjected to direct tensile force. The cohesive zone models were employed to evaluate the interfacial bond between materials. Firstly, two representative volume element models of fibers and matrix were proposed to predict engineering constants and strengths of the FRP material in three dimensions. Then, the main simulation, including the FRP rod, filling material, and steel tube, was carried out to analyze FRP rods under the variation of cohesive zone model parameters. The load-capacity, failure modes, shear-lag effect were predicted based on the maximum stress criterion. The results revealed that the FRP material strengths enforce the failure in two modes associated with the transverse and longitudinal directions of FRP rods. In addition, diameter is a significant factor that increases the shear-lag effect and reduces the tensile strength of the FRP rods. The numerical simulation provided a new method to predict the load-capacity of FRP rods.